Increase in Ventricle Size and the Evolution of White Matter Changes on Serial Imaging in Critically Ill Patients with COVID-19 - Agarwal, Shashank (Neurocrit Care, 2021)
BACKGROUND: Evolution of brain magnetic resonance imaging (MRI) findings in critically ill patients with coronavirus disease 2019 (COVID-19) is unknown. METHODS: We retrospectively reviewed 4530 critically ill patients with COVID-19 admitted to three tertiary care hospitals in New York City from March 1 to June 30, 2020 to identify patients who had more than one brain MRI. We reviewed the initial and final MRI for each patient to (1) measure the percent change in the bicaudate index and third ventricular diameter and (2) evaluate changes in the presence and severity of white matter changes. RESULTS: Twenty-one patients had two MRIs separated by a median of 22 [Interquartile range (IQR) 14–30] days. Ventricle size increased for 15 patients (71%) between scans [median bicaudate index 0.16 (IQR 0.126–0.181) initially and 0.167 (IQR 0.138–0.203) on final imaging (p < 0.001); median third ventricular diameter 6.9 mm (IQR 5.4–10.3) initially and 7.2 mm (IQR 6.4–10.8) on final imaging (p < 0.001)]. Every patient had white matter changes on the initial and final MRI; between images, they worsened for seven patients (33%) and improved for three (14%). CONCLUSIONS: On serial imaging of critically ill patients with COVID-19, ventricle size frequently increased over several weeks. White matter changes were often unchanged, but in some cases they worsened or improved, demonstrating there is likely a spectrum of pathophysiological processes responsible for these changes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12028-021-01207-2.